Fluctuating Asymmetry of Red Tilapia (Oreochromis niloticus) in Genteng Fish Hatchery Center, Banyuwangi - Darmawan Setia Budi; Lailatul Lutfiyah; Rr. Juni Triastuti (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Fluctuating asymmetry of bilateral meristic characteristic is one of the simple methods that can be used to determine the stability of an individual fish development. This study aims to provide quantitative information about the level of asymmetry red tilapia (Oreochromis niloticus) in Genteng Fish Hatchery Center through bilateral meristic characteristic observation. The number of fish used in this study is 100 fish which have a measurement of 5-7 cm. Bilateral meristic characteristic observed is the number of soft pectoral fins, the number of soft pelvic fins, and the number of scales on the lateral line. The results show that the highest value of the fluctuating asymmetry magnitude (FAm) and fluctuating asymmetry number (FAn) are obtained at the number of scales on the lateral line those are 3.71 and 0.86. Furthermore, on soft pectoral fins, the FAm value obtained is 1.29 and the FAn value is 0.58. Meanwhile, the lowest FAm and FAn values obtained from the soft ventral fins which are 0.93 and 0.50. The overall FAm value is 5.93 and the overall FAn value is 1.94.